New quinoxalinone inhibitors targeting secreted phospholipase A2 and alpha-glucosidase - Alasmary, Fatmah A.S.; Alnahdi, Fatima S.; Ben Bacha, Abir G.; El-Araby, Amr M.; Moubayed, Nadine Ms; Alafeefy, Ahmed Mahmoud; El-Araby, Moustafa E. (Informa Healthcare, 2017)
Elevated blood glucose and increased activities of secreted phospholipase A2 (sPLA2) are strongly linked to coronary heart disease. In this report, our goal was to develop small heterocyclic compound that inhibit sPLA2. The title compounds were also tested against α-glucosidase and α-amylase. This array of enzymes was selected due to their implication in blood glucose regulation and diabetic cardiovascular complications. Therefore, two distinct series of quinoxalinone derivatives were synthesised; 3-[N′-(substituted-benzylidene)-hydrazino]-1H-quinoxalin-2-ones 3a–f and 1-(substituted-phenyl)-5H-[1,2,4]triazolo[4,3-a]quinoxalin-4-ones 4a–f. Four compounds showed promising enzyme inhibitory effect, compounds 3f and 4b–d potently inhibited the catalytic activities of all of the studied proinflammatory sPLA2. Compound 3e inhibited α-glucosidase (IC50 = 9.99 ± 0.18 µM); which is comparable to quercetin (IC50 = 9.93 ± 0.66 µM), a known inhibitor of this enzyme. Unfortunately, all compounds showed weak activity against α-amylase (IC50 > 200 µM). Structure-based molecular modelling tools were utilised to rationalise the SAR compared to co-crystal structures with sPLA2-GX as well as α-glucosidase. This report introduces novel compounds with dual activities on biochemically unrelated enzymes mutually involved in diabetes and its complications.